ADVERSE REACTIONS TO ANTIMICROBIAL AGENTS IN INTERNAL MEDICINE AND ORTHOPEDIC SERVICES. JOSINA MACHEL HOSPITAL, 2014 - Mateus Sebastião João Fernandes; Héctor Lara Fernández; Vladimir Calzadilla Moreira (Formifarma, LDA., 2015)
A descriptive, prospective study was conducted to characterize the incidence and type of Adverse Drug Reactions (ADR) to antimicrobial agents in patients hospitalized in internal medicine and Orthopedic services at "Josina Machel" Central Hospital, in Luanda, in the period from January to February 2014 . The occurrence of adverse drug reactions was assessed by daily review of the clinical history of the patients with active search for potentially adverse effects associated with prescription antimicrobial agents. Of a total of 206 hospitalized patients, 21 were affected by ADR, corresponding to an incidence rate of 10.2%. The incidence was significantly higher in the internal medicine service, occurring in 11.7% of 137 patients admitted, while in the orthopedic service the incidence was 7.2% (5/69). The highest incidence of ADR was recorded in patients aged 30-39 years in 10 patients (4.9%), and in the female gender (7.8%). The most common clinical manifestations of ADR were rash (17.2%), followed by headache, pruritus and nausea and vomiting (13.8%). The antimicrobials most frequently associated with the occurrence of ADR were the antimalarial, related to more than half the cases. Among the antibacterial agents cephalosporins were associated to five cases of ADR (23.8%). Most ADR were classified according to severity as mild (52.4%) and as probable (57.1%) regarding the attribution of causality. Given the growing impact of the occurrence of ADR we recommend pursuing this research, in order to further deepen this problem.